Sino-U.S. Strategic Competition in the Indo-Pacific: Is it Thucydides’ Trap? (Journal of International Relations and Peace, 2024)
This paper aims to analyze the Sino-U.S. rivalry and the possibility of hot conflict. The realist scholars analyzed the current paradigm through the lens of the realist perspective. The realist views it in the context of the U.S.-USSR, Cold War, and ‘Thucydides’ Trap. In contrast, the liberalist views it with the liberalist spectrum. Scholars view the current rivalry in the old theories, like the previous chronicles, such as the Thucydides trap and the Cold War. However, they may analyze the paradigm from new angles, with ground facts. Find the solution in between the realist and liberalist points of view. Strategic competition does not mean war and destruction; it implies that powers compete in geopolitics. The term Strategic Competition came into practice during the détente era, in the 1970s, when both powers i.e. the US and USSR were in a tough Cold War rivalry, but through negotiation, tension was reduced. The U.S-China are in strategic competition and they will reduce the rivalry and not go to war. China wants to gain superpower status without war, believing Sun Tzu’s philosophy ‘To win without fighting is better than winning with losses’. It’s normal in international relations that powers achieve their interest through military power, diplomacy, trade, and aid. Power, helps states to get tactical and bargaining leverage. China’s behavior and pattern show that China did not colonize foreign land, noninterference foreign policy, and did not influence its economic or political ideology on other governments. Hence, there is no possibility of Thucydides ’trap.